Using advanced tomography techniques to investigate the development of White Etching Cracks in a prematurely failed field bearing. (December 2017) - Gould, Benjamin; Greco, Aaron; Stadler, Kenred; Vegter, Erik; Xiao, Xianghui
Abstract: Crack surrounded by areas of microstructural alteration deemed "White Etching Cracks" (WECs) lead to premature failures within a multitude applications. While the exact cause of these failures remains unknown, a large number of hypotheses exist as to how and why these cracks form. The aim of the current work is to study newly initiated WEC networks using X-ray tomography followed by selective sectioning, in an attempt to elucidate the formation mechanisms of these cracks. The results obtained show that, for the presented bearing, WECs form preferentially around multi-phase inclusions containing aluminum, manganese, and sulfur. Additionally the results support the idea that the microstructural alterations form secondary to any cracking, suggesting that the alterations are simply a symptom of a pre-existing failure. Highlights: Four white etching crack (WEC) networks were identified using X-Ray tomography. All WECs were initiated at multiphase inclusions containing Al, Mn, and S. The microstructural alterations are a consequence of a preexisting crack. Additional processes can be used to rid bearings of these inclusions.